2021
DOI: 10.3390/ijerph182111593
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Atopic Dermatitis on Health-Related Quality of Life in Bangladesh

Abstract: Atopic dermatitis (AD) is the foremost non-fatal skin-related disease that affects all age groups. Despite the growing prevalence of AD in low- and middle-income countries, its physiological consequences remain overlooked in countries like Bangladesh. Therefore, we aim to assess and characterize the influence of AD on the health-related quality of life (HRQoL) in Bangladeshi patients. A cross-sectional study comprising 184 eligible adults (83 men and 101 women; mean age, 33.46 ± 15.44 years) was conducted at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These results emphasize the necessity of managing AD with a more patient-centric strategy in order to reduce patient suffering and enhance HRQoL. 16 Results as reported by patients Clinical trial measures make ensuring that essential patient outcomes are the focus of efficacy assessments. Repeated assessments may provide a more accurate picture of the disease load and treatment efficacy than less frequent measures in relapsing-remitting disorders like eczema.…”
Section: Discussionmentioning
confidence: 83%
“…These results emphasize the necessity of managing AD with a more patient-centric strategy in order to reduce patient suffering and enhance HRQoL. 16 Results as reported by patients Clinical trial measures make ensuring that essential patient outcomes are the focus of efficacy assessments. Repeated assessments may provide a more accurate picture of the disease load and treatment efficacy than less frequent measures in relapsing-remitting disorders like eczema.…”
Section: Discussionmentioning
confidence: 83%
“…In total, 12 articles reporting on 12 different PROMs in 45 single studies on measurement properties were analyzed 18,26,28–37 …”
Section: Resultsmentioning
confidence: 99%
“…In total, 12 articles reporting on 12 different PROMs in 45 single studies on measurement properties were analyzed. 18,26,[28][29][30][31][32][33][34][35][36][37] Relevant characteristics of the identified PROMs, such as number of items, recall period, response categories, and target population., are presented in Appendix S3. Relevant characteristics of the included study populations can be found in Appendix S4.…”
Section: Data Extractionmentioning
confidence: 99%